2007
DOI: 10.1016/j.ijthermalsci.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation on NOX formation in counterflow n-heptane triple flames

Abstract: /npsi/ctrl?action=rtdoc&an=6597458&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=6597458&lang=frAccess and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In this study, the NO x formation submodel of Glarborg and co-workers was incorporated into the aforementioned fuel-related kinetic models. In order to identify the relative importance of each NO x formation route, the technique of Guo and Smallwood , was utilized, which involves a number of simulations. It is established now that the initiation steps for NO x formation are as follows (e.g., refs ) normalN 2 + normalO normalN + NO .25em ( Thermal route ) CH + normalN 2 NCN + normalH .25em ( Prompt route ) normalN 2 + normalO + normalM normalN 2 normalO + normalM .25em ( N 2 O route ) normalN 2 + OH normalN 2 normalO + normalH .25em ( N 2 O route ) normalN 2 + normalO 2 normalN 2 normalO + normalO .25em ( N 2 …”
Section: Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the NO x formation submodel of Glarborg and co-workers was incorporated into the aforementioned fuel-related kinetic models. In order to identify the relative importance of each NO x formation route, the technique of Guo and Smallwood , was utilized, which involves a number of simulations. It is established now that the initiation steps for NO x formation are as follows (e.g., refs ) normalN 2 + normalO normalN + NO .25em ( Thermal route ) CH + normalN 2 NCN + normalH .25em ( Prompt route ) normalN 2 + normalO + normalM normalN 2 normalO + normalM .25em ( N 2 O route ) normalN 2 + OH normalN 2 normalO + normalH .25em ( N 2 O route ) normalN 2 + normalO 2 normalN 2 normalO + normalO .25em ( N 2 …”
Section: Modeling Approachmentioning
confidence: 99%
“…In this study, the NO x formation submodel of Glarborg and coworkers 45 was incorporated into the aforementioned fuelrelated kinetic models. In order to identify the relative importance of each NO x formation route, the technique of Guo and Smallwood 46,47 was utilized, which involves a number of simulations. It is established now that the initiation steps for NO x formation are as follows (e.g., refs 45−47)…”
Section: Modeling Approachmentioning
confidence: 99%
“…To model NO x formation, two different sets of kinetics are tested after they are incorporated into the aforementioned combined model, namely, the one included in GRI 3.0, hereinafter referred to as Model 1, and that of Glarborg and co-workers, referred to as Model 2. To identify the relative importance of each NO x formation route, the technique of Smallwood and co-workers , was utilized.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The study is motivated by several considerations. The first is that fundamental flame investigations dealing with large hydrocarbons have mostly considered saturated fuels, such as heptane. Another motivation is due to the importance of triple flames in numerous practical applications. Such flames play a fundamental role in characterizing lifted jet flames as well as the propagation and stabilization of laminar and turbulent flames. , Such flames are also relevant to diesel engine combustion, especially in the context of novel low-temperature combustion concepts, including homogeneous charge compression ignition (HCCI), premixed charge compression ignition (PCCI), and dual-fuel injection.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas triple flames burning smaller hydrocarbon fuels have been extensively investigated, there have been few studies dealing with large hydrocarbon fuels. Guo and Smallwood 16 numerically investigated n-heptane triple flames and observed that a large amount of prompt NO is formed in the rich premixed flame branch. They also discussed interactions involving heat and species transport between the three reaction zones.…”
Section: Introductionmentioning
confidence: 99%